Health determinants in the quality of life of older adults in the 24 de Mayo canton, Manabí - Armas, Tyron; Pin, María G.; García, Nahomy A.; Roldán, Milka A.; Chimbo, Patricio J. (Revista Gregoriana de Ciencias de la Salud, 2024)
The objective of this research was to identify the main health determinants affecting older adults in Manabí, with a special focus on chronic diseases, quality of life, and socioeconomic factors. The results show high levels of stress, anxiety, and depression, exacerbated by excessive alcohol and tobacco consumption. Additionally, insufficient sleep patterns negatively impact their overall well-being. In terms of nutrition, their diet, primarily based on carbohydrates, reflects economic limitations and restricted access to fresh foods, leading to potential nutritional imbalances. Although some express satisfaction with health services, a significant proportion believes that care does not meet their needs, highlighting deficiencies in resources and infrastructure. These issues underline the need to implement comprehensive policies that promote the well-being of this vulnerable group, addressing emotional, behavioral, social, and economic aspects to ensure their quality of life and respect for their rights.